Analysing the acoustic evidence of consonant productions among students at the university level - Nur'Aini, Siti (LITERA, 2024)
Learners of English as a second language (L2) whose first language (L1) is Indonesian tend to struggle to produce aspirated consonants. This study investigates whether the difficulties came from the interference of the L1 for the production of these sounds: [k], [b], [d], [g] in the final positions, and [p] and [t] in the stressed syllable. This study involved two cohorts of English department university students with different levels of fluency in L2 speech production. The L2 learners were asked to pronounce 25 words from a textbook previously used to teach them. The L2 learners were exposed to a British English-speaking speech model, which became a benchmark for the L2 learners' pronunciation by asking them to imitate the pronunciation. Annotation of data was conducted twice by a second annotator to ensure the objectivity of the scores given to the L2 learners which was analised using paired sample t-test. Findings suggest that the sounds with the lowest success rate of production were [p] in the stressed syllable, [k], and [g] in the final position. The production was unsuccessful because the L2 learners did not have phonological awareness of how the L2 consonant sounds were produced near-natively and were affected by their L1. The lack of awareness led to the failure to produce [p], [k], and [g] sounds because these sounds did not exist in their L1 and interference of the L1 was embed to the L2 speech production. The format analysis results using PRAAT indicate that there is an improvement in the participants' pronunciation after exposure to the native speaker's speech sound. The implication of this research is paramount for L2 learners and lecturers in highlighting the importance of targeted instruction and intervention to address the challenges in speech production. Contrasting the phonetic features of L1 and L2 sounds helped the learners to defer interference in their L2 speech production. This study encourages continuous assessment of L2 learners to ensure that they maintain the consistency of speech production to sound near-native.